Implementation of merdeka curriculum in fostering entrepreneurial interest of vocational students - Bambang Sudarsono; Imam Rosyidin (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to develop an industry-based Merdeka curriculum management model (MKBI) to foster entrepreneurial interest among vocational school students, while addressing the challenges of low graduate employability and limited curriculum integration with industry needs. The research method employs the Research and Development (R&D) model by Richey and Klein, comprising three main stages: (1) needs analysis through three Focus Group Discussions (FGDs) involving vocational high school teachers, industry practitioners, and the Education Department; (2) conceptual design of the MKBI model incorporating four core competencies (technical, marketing, financial, and human relations) along with supporting infrastructure and technology; and (3) model validation by curriculum experts and industry practitioners using a scale-based feasibility questionnaire. The research results indicate that, conceptually, 100% of experts stated that the model has a strong theoretical foundation, is relevant to industry and education needs, and can enhance students' interest in entrepreneurship. In terms of benefits, 100% of experts assessed that the model makes a real contribution to improving entrepreneurial understanding and skills and can be applied in various vocational school departments. In terms of practical feasibility, 67% of experts assessed that the implementation guidelines are clear, while 33% assessed that improvements are needed to facilitate implementation in schools with limited resources. The implications of this research are the need for continuous adaptation to technological developments and industry needs, strengthening school-industry partnerships, and providing measurable evaluation systems such as indicators of the number of students who start businesses after graduation or participate in entrepreneurship projects during their studies. The MKBI model developed has the potential to serve as a national benchmark for enhancing the relevance of vocational education, reducing unemployment among SMK graduates, and cultivating a competent and entrepreneurial-ready younger generation.